Implementation of Microservices Architecture on E-Commerce Web Service - Juan Andrew Suthendra; Magdalena Ariance Ineke Pakereng (Bina Nusantara University, 2020)
The research aimed to make e-commerce web services using a microservices architecture. Web service was built using Representational State Transfer Protocol (REST) with Hypertext Transfer Protocol (HTTP) method and JavaScript Object Notation (JSON) response format. Meanwhile, the microservices architecture was developed using Domain-driven Design (DDD) approach. The research began by analyzing e-commerce business processes and was modeled using Unified Modeling Language (UML) based on business process analysis. Next, the bounded context was used to make a small responsible service for a function. The Programming language used to make the system was Go programming language with Go-kit tool and apply database-per-service pattern for data management. The system also applied the concept of containerization using Docker as the container platform and using API Gateway to manage each endpoint. Last, the evaluation process was carried out using the Postman application by testing each endpoint based on the white-box testing method. Based on the results of the evaluation process, the e-commerce web service can work as expected. The results also show that the system has a high level of resilience. It means that the system has a low level of dependencies between services and adapts to future changes.